Strategic Issues & Recommendations for The Eve Appeal - Marler, Christine (2011)
The charity sector, also known as the third sector, has grown significantly over the course of the past decade and sits primarily between the private and public sectors. This sector plays an important role in society and the economy as it brings in over £28 billion in income annually and generates over 611,000 jobs (Graduate Prospects Ltd., 2011).